การวิเคราะห์คุณค่ารายการ "ครอบครัวเดียวกัน" ในการส่งเสริมสถาบันครอบครัว - อุษารัตน์ อินทร์พงษ์พันธุ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This study aims to analyze 1) the content of television program "My Family" 2) the program’s value in promoting family institution. This qualitative research employs Textual Analysis to analyze content of 48 episodes of "My Family" airing via ThaiPBS television channel during the year 2010. This assessment of program’s value bases on the concept of family institution and family relation. The result of this research shows that the program conveys the diverse stories of families in Thai society as the main content with emphasizing on the power of beautiful relation in those families i.e. love, understanding, caring, warm feeling, and good communication. This beautiful relation in the family can empower family members not only solving their problems but also bringing happiness and security to those families, communities and, ultimately, societies. The research also finds that the program’s value in promoting family institution is associate with the 3 kinds of powerful message that result in 1) the awareness of families’ roles and their importance, 2) broad family’s definition 3) showing the power of family relation in promoting family institution. Finally, the stories of invited families as well as program’s guest speakers, who can convey both sensational message of life and the great concept learned from them, are the key element of powerful message and its value.